Editorial: importance of an elevated mean platelet volume for prediction of major adverse cardiovascular events in non‐alcoholic fatty liver disease – authors' reply. Issue 8 (28th March 2019) - Mullish, Benjamin H.; Forlano, Roberta; Abeles, Robin Daniel; Thursz, Mark R.; Manousou, Pinelopi
Abstract : Linked Content This article is linked to Abeles et al and Targher and Lippi papers. To view these articles, visithttps://doi.org/10.1111/apt.15192, andhttps://doi.org/10.1111/apt.15208 .